Acute thrombosis during carotid artery stenting caused by stent-induced kinking - Chrapkowska, Magdalena; Modrzejewski, Andrzej (Global Journal of Medical and Clinical Case Reports, 2021)
A case of a 71-year-old man with previous Transient Ischemic Attack (TIA), treated with stent implantation due to right internal carotid artery stenosis. The procedure was complicated by stenosis and kinking of the vessel distal to the stent and thrombus formation. The flow in the stented artery was not restored. A massive stroke occurred. The man died on the 3rd day after the procedure.